Effects and interventions regarding the therapy in relation to the addiction of gambling - Avram, Florentina; Sandu, Mihaela Luminita; Punga, Valentina (Technium Social Sciences Journal, 2021)
In nowadays society, gambling and bets are a type of entertainement socially accepted, but the risk that their usage turn into an unrestrained practice with several negative consequences turned gambling into a subject for psychologists and sociologs. The reason for choosing this subject was generated by the need of pointing out the serious problem of gambling addiction with which more and more people have been confronting lately and which affects addicted gamblers, their families and the entire Romanian society. When a person starts gambling more and more and uses more money for it at the expense of the other daily activities, one could state that this person adopts and develops an unduly and compulsive behavior that might become addictive. The consequences of gambling addiction vary from financial problems to increased or prolonged stress, to disrupted families, wasted fortunes, destroyed lives, dropouts, and it is more and more important that, especially, the young generation, but also the rest of the population that gambles more and more in the arcades and casinos realise the importance of a responsable gambling and how to avoid addictions.